Strategies for handling ethical problems in end of life care: obstacles and possibilities. (November 2015) - Rejnö, Åsa; Berg, Linda
Background: In end of life care, ethical problems often come to the fore. Little research is performed on ways or strategies for handling those problems and even less on obstacles to and possibilities of using such strategies. A previous study illuminated stroke team members' experiences of ethical problems and how the teams managed the situation when caring for patients faced with sudden and unexpected death from stroke. These findings have been further explored in this study. Objective: The aim of the study was to illuminate obstacles and possibilities perceived by stroke team members in using strategies for handling ethical problems when caring for patients afflicted by sudden and unexpected death caused by stroke. Research design: A qualitative method with combined deductive and inductive content analysis was utilized. Participants and research context: Data were collected through individual interviews with 15 stroke team members working in stroke units of two associated county hospitals in western Sweden. Ethical considerations: The study was approved by the Regional Ethics Review Board, Gothenburg, Sweden. Permission was also obtained from the director of each stroke unit. Findings: All the studied strategies for handling of ethical problems were found to have both obstacles and possibilities. Uncertainty is shown as a major obstacle and unanimity as a possibility in the use of the strategies. The findings also illuminate the value of the concept "the patient's best interests" as a starting point for the carers' ethical reasoning. Conclusion: The concept "the patient's best interests" used as a starting point for ethical reasoning among the carers is not explicitly defined yet, which might make this value difficult to use both as a universal concept and as an argument for decisions. Carers therefore need to strengthen their argumentation and reflect on and use ethically grounded arguments and defined ethical values like dignity in their clinical work and decisions.